'Tutored within an inch of their life': morality and 'old' and 'new' middle class identities in Australian schools. Issue 14 (26th October 2017) - Butler, Rose; Ho, Christina; Vincent, Eve
ABSTRACT: This paper documents the self-positioning of a segment of middle class parents, whom we call 'community-minded', as they distinguish themselves from pedagogies and parenting practices for education often associated with 'tiger parenting' and 'Asian' practices in Australia. Increased public interest has scrutinised the growth of high achieving Asian-Australian students and commonly depicts 'Asian success' as being about ethnicity and/or race. As academics argue, such essentialism validates existing capitals among middle-class parents and feeds into a politics of racial hostility. Building on this literature, we focus on this site of tension as one of a struggle between 'old' and 'new' middle classes. Drawing on a small study in Sydney NSW, we deal with a fraction of the middle classes for whom particular educational strategies are disavowed as part of their self-positioning as moral, 'community-minded' citizens. This is analysed as a response to broader changes across education, the economy and migration trajectories which have emerged alongside what Watkins and Noble call the 'ethnicisation' of academic achievement. These tensions provide insight into how 'old' and 'new' middle classes are attempting to co-exist in Australian schools, as global political and economic transformations are negotiated within the micropolitics of parenting and cultural constructions of childhood.